The outcomes of isolated thoracolumbar burst fractures without neurological deficit comparing between operative and non-operative treatments - Tharumaraja, Thiruselvam (2008)
Thoracolumbar fractures make up 40% of all spine fractures, usually arising from high energy trauma. This includes the region from thoracic 11 to lumbar 2 Vertebra. The thoracolumbar junction is situated between the rigid thoracic spine and the relatively mobile lumbar spine, predisposing it to injury. The treatment for burst thoracolumbar fractures with no neurological deficit has always been a controversy. This study is to evaluate the functional outcomes in operative versus non-operative treatment in thoracolumbar burst fractures at a single level, with no neurological deficit. The study was conducted over a period of 1 year, The parameters studied are pain, time taken to return to previous job and progression of kyphotic deformity. This study was conducted at Hospital Tengku Ampuan Afzan, Kuantan, Pahang and Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan.